Evaluation of Consumer Attitudes: Attributes of Langsa Hutan Lindung Park Tourism Services - Suri Amilia; Muhammad Rizqi Zati; Dhian Rosalina (Universitas Pendidikan Ganesha, 2023)
Attitude is a combination of motivation, emotion, and perception of an aspect of an individual's life. Consumer attitude is an emotional expression of consumers that shows whether consumers like an object or not so that attitudes can describe the level of consumer confidence in products or services. Consumer attitudes on tourism service attributes describe what priority attributes are taken into consideration in choosing and visiting tourist sites. The purpose of this study is to analyze consumer attitudes towards the Langsa hutan lindung park tourism services. This research is a quantitative descriptive using Fishbein's multi-attribute method. Fishbein's Multiattribute Model can measure consumer attitudes using three components: the level of importance, trust, and attitude evaluation. There are one hundred tourists who are visiting and selected using accidental sampling. The results of this study indicate that research respondents have a positive attitude towards all fourteen attributes of protected forest tourism marketing services, and two of them are very positive about two attributes: the level of crime rate and the spacious parking lots.